The Movable Nosaic: Aa Inquiry Into The Theory of Reconstruction of Political Reality - Kroker, Arthur William (My University, 1975)
The dissertation is devoted to the development of a systematic theory of political experience. While this project involves, at first, the synthesis of the pragmatist tradition in political philosophy into a theory of reconstructive empiricism, it also entails the elaboration of this revision of political epistemology into a paradigmatic theory of human action. Using this paradigmatic theory of human action as the basis of analysis, an examination then follows of three generalized modes of political experience, and of the relationships which hold between them.
Keywords: Movable mosaic; Political reality